2010
DOI: 10.1371/journal.pone.0010904
|View full text |Cite
|
Sign up to set email alerts
|

Q344ter Mutation Causes Mislocalization of Rhodopsin Molecules That Are Catalytically Active: A Mouse Model of Q344ter-Induced Retinal Degeneration

Abstract: Q344ter is a naturally occurring rhodopsin mutation in humans that causes autosomal dominant retinal degeneration through mechanisms that are not fully understood, but are thought to involve an early termination that removed the trafficking signal, QVAPA, leading to its mislocalization in the rod photoreceptor cell. To better understand the disease mechanism(s), transgenic mice that express Q344ter were generated and crossed with rhodopsin knockout mice. Dark-reared Q344terrho+/− mice exhibited retinal degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 61 publications
2
82
1
Order By: Relevance
“…We investigated this possibility in a transgenic mouse line that expressed Gln334 → stop (Q344ter). We found that Q344ter is a substrate for light-dependent phosphorylation in the IS/ONL compartments, but in this case, preventing formation of rhodopsin/arrestin complex by raising the mice in darkness had little effect on retinal degeneration (39). Rhodopsin mislocalization also occurs when its transport machinery is defective, such as in the case of functional loss of kinesin-2, a major motor for anterograde transport (44).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We investigated this possibility in a transgenic mouse line that expressed Gln334 → stop (Q344ter). We found that Q344ter is a substrate for light-dependent phosphorylation in the IS/ONL compartments, but in this case, preventing formation of rhodopsin/arrestin complex by raising the mice in darkness had little effect on retinal degeneration (39). Rhodopsin mislocalization also occurs when its transport machinery is defective, such as in the case of functional loss of kinesin-2, a major motor for anterograde transport (44).…”
Section: Discussionmentioning
confidence: 84%
“…Rhodopsin mislocalization also occurs in a different class of naturally occurring, disease-causing mutations at its carboxyl terminus (39)(40)(41). These mutants form a visual pigment with 11-cis retinal and activate transducin in a light-dependent manner (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…This is an evolutionarily conserved motif implying a vital function. A number of studies in transgenic animals have shown that these mutant rhodopsins mislocalize to the plasma membrane of the RIS while properly localizing to the ROS discs (10,11). Nakao et al have shown that when mutant zebrafish expressing the Class I mutation Gln344Ter are reared in the dark (i.e.…”
Section: Retinitis Pigmentosa (Rp)mentioning
confidence: 99%
“…(1) The absence of a gene versus a dominant-negative action often has different effects ex vivo (in cellular models) and in vivo e.g. even retinas of a rhodopsin hypomorph mouse develop normally, rods elaborate ROS of normal size, and retinas look identical to controls at P41, whereas comparable expression of a dominant negative mutant affecting the VxPx CTS of rhodopsin causes retinal degeneration modeling ADRP (Concepcion and Chen, 2010;Concepcion et al, 2002;Humphries et al, 1997;Lem et al, 1999;Li et al, 1996). (2) The volume of membrane trafficking in the frog eye exceeds by an order of magnitude that of the rodent rods.…”
Section: Discussionmentioning
confidence: 99%